Developing Preservice Biology Teachers' Creative Thinking Skills Through Integrating E-Books into Problem-Based Learning - Sirajudin, Nuraini; Tolla, Ismail; Muharram (Science Education and Application Journal, 2024)
Developing Preservice Biology Teachers' Creative Thinking Skills Through Integrating E-Books into Problem-Based Learning. This research aims to find a low solution quality of teachers in North Maluku Province, Indonesia. One alternative proposed is integrating e-books into problem-based learning to see the impact on preservice biology teachers' creative thinking skills. Pre-experiment-bookstall research methodology and one group's pretest-posttest design are used. This research was carried out in 2024, and the research location was the Study Program for Biology Education, University of Khairun, Indonesia. The research subjects were preservice biology teachers. The selection of research subjects was based on the initial ability level (high, medium, low), so the number of research subjects was 6 (2 groups). The research results concluded that integrating e-books into a problem-based learning model was very effective in improving the creative thinking skills of preservice biology teachers. Further research also makes it possible to see the differences in the effect of providing learning activity links (e-books) before or after offline lectures are conducted.